2017
DOI: 10.1017/s0022029916000832
|View full text |Cite
|
Sign up to set email alerts
|

Association of MAP4K4 gene single nucleotide polymorphism with mastitis and milk traits in Chinese Holstein cattle

Abstract: The objective of the studies presented in this Research Communication was to investigate the association of single nucleotide polymorphisms present in the MAP4K4 gene with different milk traits in dairy cows. Based on previous QTL fine mapping results on bovine chromosome 11, the MAP4K4 gene was selected as a candidate gene to evaluate its effect on somatic cell count and milk traits in ChineseHolstein cows. Milk production traits including milk yield, fat percentage, and protein percentage of each cow were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…Studies showing the important roles of SNPs for milk production traits in dairy cattle have been reported previously [8,9,10,22]. Pegolo et al discovered two SNPs, rs136905033 and rs137457402, of LPIN1 associated with milk fatty acids in bovine [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies showing the important roles of SNPs for milk production traits in dairy cattle have been reported previously [8,9,10,22]. Pegolo et al discovered two SNPs, rs136905033 and rs137457402, of LPIN1 associated with milk fatty acids in bovine [23].…”
Section: Discussionmentioning
confidence: 99%
“…Genome-wide studies in dairy cows have allowed researchers to detect quantitative trait locus (QTL) harboring candidate polymorphic genes that are involved in milk production [3,4,5]. Moreover, studies have shown that the single nucleotide polymorphisms (SNPs) in the genes clearly influenced the milk yield and composition in Holsteins [6,7,8,9,10]. These results collectively suggest that loci found to affect milk production traits could be used in marker-assisted selection programs aimed at accelerating genetic progress of dairy cattle.…”
Section: Introductionmentioning
confidence: 99%
“…Animal sampling, DNA extraction, primer design and SNP study For the initial mutation screening for exon 8 (K232A), a total of 84 blood samples including 41 cows and 43 buffaloes were used and DNA was extracted as described by Bhattarai et al (2017).…”
Section: Methodsmentioning
confidence: 99%
“…A study has revealed that the use of available loci improved the accuracy of genomic prediction in dairy cattle [19], which suggests that loci that are associated with milk production traits could be used in genomic selection programs that are aimed at accelerating genetic progress of dairy cattle. Studies have shown that the SNPs in the candidate genes significantly influenced the milk yield and composition in Holsteins [20,21,22,23,24,25]. In this study, we identified ten SNPs in NUCB2 and found that the SNPs and haplotypes of this gene were significantly associated with milk production traits.…”
Section: Discussionmentioning
confidence: 68%